Improving The Legal Mechanisms For Protecting Whistleblowers (Diversity Research: Journal of Analysis and Trends, 2026)
This article provides a comprehensive analysis of legal mechanisms for the protection of individuals who report corruption-related offenses (whistleblowers). Based on the current legislation of the Republic of Uzbekistan, the existing legal framework is examined and compared with international practices. The study identifies key problems within the national system and proposes specific legal recommendations aimed at addressing these issues